Synthesis, structure and electrical behaviour of lanthanum-doped barium stannate - Upadhyay S.; Parkash O.; Kumar D. (My University, 2025)
A few samples in the system Ba1-xLaxSnO3 (up to x ≤0.15) have been synthesized via the solid state ceramic route. Powder x-ray diffraction pattern of the samples confirm the formation of a single phase solid solution only in the samples with x up to ≤0.05. It was found that single phase compositions have a cubic crystal structure similar to that of undoped barium stannate. The ac electrical and dielectric properties of single phase samples have been studied in the frequency range 10Hz-5 MHz for temperatures ranging from 300 to 550 K. The conductivities (both ac and dc) and relaxation time (τ) exhibit two regions of temperature dependence, namely region I, which represents 300-420 K, and region II, which governs 420-550 K. Conduction and dielectric relaxation in both temperature regions are explained in terms of variable range hopping of electrons. Complex plane impedance analysis revealed that the specific conductivity of the grains is two orders of magnitude higher than that of the grain boundaries.